miR-29a Negatively Affects Glucose-Stimulated Insulin Secretion and MIN6 Cell Proliferation via Cdc42/β-Catenin Signaling - Jing Duan; Xian-Ling Qian; Jun Li; Xing-Hua Xiao; Xiang-Tong Lu; Lin-Chen Lv; Qing-Yun Huang; Wen Ding; Hong-Yan Zhang; Li-Xia Xiong (International Journal of Endocrinology)
Background. Diabetes is a progressive metabolic disease characterized by hyperglycemia. Functional impairment of islet β cells can occur to varying degrees. This impairment can initially be compensated for by proliferation and metabolic changes of β cells. Cell division control protein 42 (Cdc42) and the microRNA (miRNA) miR-29 have important roles in β-cell proliferation and glucose-stimulated insulin secretion (GSIS), which we further explored using the mouse insulinoma cell line MIN6. Methods. Upregulation and downregulation of miR-29a and Cdc42 were accomplished using transient transfection. miR-29a and Cdc42 expression was detected by real-time PCR and western blotting. MIN6 proliferation was detected using a cell counting kit assay. GSIS under high-glucose (20.0 mM) or basal-glucose (5.0 mM) stimulation was detected by enzyme-linked immunosorbent assay. The miR-29a binding site in the Cdc42 mRNA 3′-untranslated region (UTR) was determined using bioinformatics and luciferase reporter assays. Results. miR-29a overexpression inhibited proliferation (P<0.01) and GSIS under high-glucose stimulation (P<0.01). Cdc42 overexpression promoted proliferation (P<0.05) and GSIS under high-glucose stimulation (P<0.05). miR-29a overexpression decreased Cdc42 expression (P<0.01), whereas miR-29a downregulation increased Cdc42 expression (P<0.01). The results showed that the Cdc42 mRNA 3′-UTR is a direct target of miR-29a in vitro. Additionally, Cdc42 reversed miR-29a-mediated inhibition of proliferation and GSIS (P<0.01). Furthermore, miR-29a inhibited β-catenin expression (P<0.01), whereas Cdc42 promoted β-catenin expression (P<0.01). Conclusion. By negatively regulating Cdc42 and the downstream molecule β-catenin, miR-29a inhibits MIN6 proliferation and insulin secretion.